GAMBARAN OPING STRESS PADA IBU RUMAH TANGGA YANG TIDAK BEKERJA - Amitya Betty Rosalina; Iriani Indri Hapsari (Journal of Research and Measurement in Psychology, 2012)
AbstrackThis study aims to look at the picture of stress coping housewife in Jakarta. Subjects were housewives who donot work and settled in DKI Jakarta. The approach used in this research is descriptive quantitative. Using samplingtechniques of non-probability sampling later in the sampling method using quota sampling. Techniques of data analysisusing descriptive analysis of data using SPSS software version 16.Total sample of 150 people. Quantitative data collection techniques used is to use questionnaires withdescriptive statistical analysis techniques research.The results of this study are coping stess is predominantly used by respondents are the Emotion FocussedCoping strategies as much as 53 respondents. For those aspects of the most widely used of the respondents are aspectsEscape / Avoidance for Emotion Focused Coping strategies. While the Problem Focused Coping strategies, aspects of themost widely used is Seeking Social Support.Keywords: Coping with Stress, Housewife That Does not Work, DKI, Jakarta